(untitled) (BIRDEM Medical Journal, 2017)
Background: Management of type 2 diabetes is not uniform. The aim of the study was to assess diabetes care delivery and status of long-term diabetes related complications. Methods: DiabCare is an observational, non-interventional, cross-sectional study of hospital-based outpatient type 2 diabetes care. Results: A total of 2092 patients participated in the study: mean age 51.3±11.0 years, and duration of diabetes 7.6±5.4 years. The patients were almost equal in both genders (male: 49.8% vs. female: 50.2%) and the largest homogenous ethnic group was Bangladeshi (99.6%). The percentage of patients with HbA1c < 7.0% (< 53 mmol/mol) was 22.5% and mean HbA1c was 8.8±2.2 %. The proportion of patients using insulin was 58.0% (n=1214) at a total daily dose of 34.4±14.7 IU. The most common diabetes related complications were: Peripheral neuropathy (39.0%) and eye complications (21.7%). Duration of diabetes was associated with higher odds of CV complications, diabetic nephropathy and eye complications [adjusted OR 1.03, p=0.007; 1.05, p<0.001 and 1.05, p<0.001 respectively]. Age also has emerged as a significant predictor for these complications. More than half of patients (56.1%) indicated their concerns about hypoglycaemia. A large proportion of patients were non-adherent to clinical recommendations. Conclusions: Poor glycaemic and metabolic control over a long period of time contributes to chronic diabetic complications. This underpins the need to further optimise the control strategies and maintain quality diabetes management standards in Bangladesh and also improving awareness among health professionals with intensive education programs for diabetes subjects is also recommended. Birdem Med J 2017; 7(1): 17-27